Biofilm formation on restorative materials and resin composite cements. Issue 11 (November 2018) - Astasov-Frauenhoffer, Monika; Glauser, Stephanie; Fischer, Jens; Schmidli, Fredy; Waltimo, Tuomas; Rohr, Nadja
Highlights: Biofilm formation on restorative and cement materials strongly relies on the materials composition. Biofilm formation is increased for materials with a high wettability by saliva/serum proteins and water. A higher organic ratio of the restorative or cement material leads to less biofilm formation. A higher ceramic content results in an increased polar part of the surface free energy of the material surface. Abstract: Objectives: Monolithic zirconia, polymer-infiltrated ceramic and acrylate polymer cemented with resin composite cement have recently been identified as prosthetic treatment options for zirconia implants. The aim of the present study is to determine in vitro, to what extent bacteria adhere to these materials. Methods: Disks made of zirconia (Vita YZ [YZ]), polymer-infiltrated ceramic (Vita Enamic [VE]), acrylate polymer (Vita CAD-Temp [CT]), self-adhesive cement (RelyX Unicem 2 Automix [RUN]) and of two different adhesive cements (RelyX Ulimate [RUL] and Vita Adiva F-Cem [VAF]) were produced. The biofilm formation of three bacterial species ( Streptococcus sanguinis, Fusobacterium nucleatum, Porphyromonas gingivalis ) on each material was assessed over 72 h using a flow chamber system. The biofilms were quantified by crystal violet staining (optical density 595 nm) and visualized using SEM. The inorganic composition of the different materials was analyzed and the wettability of the specimens was measured. Results: For the restorative materials lowest biofilm formation was found on CT: OD 0.5 ± 0.1, followed by VE: OD 0.8 ± 0.1 and YZ: OD 1.4 ± 0.3. The biofilm formation on resin composite cements was significantly lower on VAF: OD 0.6 ± 0.1 than for RUL: OD 0.9 ± 0.1 and RUN: OD 1.0 ± 0.1. A high wettability of the specimens with saliva/serum mixture tended to result in a higher biofilm formation. Correlations were obtained between the organic/inorganic composition of the materials and the polar/dispersive part of the surface free energy. Significance: Three-species biofilm formation on restorative and cement materials strongly relies on the materials composition. If the restorative material CT and cement VAF also prevent excessive biofilm formation in a clinical situation should be further investigated.